Mencengkeram Indonesia: Pengaruh Amerika Serikat Terhadap Kebijakan IMF Masa Krisis Ekonomi 1997-1998 - Santoso, Fajar (Prabayaksa: Journal of History Education, 2024)
Indonesia has a rich and intricate history, with one notable period being the 1997-1998 economic crisis. Originating from Thailand, the economic crisis spread to neighboring countries, including Indonesia. Despite seeking assistance from the IMF to mitigate the crisis, Indonesia struggled to revive its economy. This article seeks to address the role of the United States in IMF policies during the 1997-1998 economic crisis in Indonesia. This research tackles the following key questions: (1) What were the socio-economic and political conditions of Indonesia during the 1997-1998 crisis? (2) How did the United States respond to Indonesia's conditions during the crisis? (3) What influence did the United States wield over IMF policies in dealing with Indonesia's economic crisis in 1997-1998? This study employs historical research methods, including topic selection, heuristics, criticism, interpretation, and historiography. The findings reveal several significant points. Firstly, the depreciation of the rupiah against the dollar led to price hikes in basic commodities, widespread layoffs, and social unrest, ultimately resulting in Soeharto's resignation as president on May 21, 1998. Secondly, the United States responded to Indonesia's economic and political conditions due to perceived deviations from democratic principles, human rights violations, and its interest in safeguarding American investment projects in Indonesia. Thirdly, the United States pressured Indonesia to accept IMF conditions and abstain from implementing the CBS system. Soeharto's resignation as president was also influenced by the United States, leveraging human rights issues and the promotion of democratic values.